Alteration in cellular turnover and progenitor cell population in lacrimal glands from thrombospondin 1−/− mice, a model of dry eye. (December 2016) - Shatos, Marie A.; Hodges, Robin R.; Morinaga, Masahiro; McNay, David E.; Islam, Rakibul; Bhattacharya, Sumit; Li, Dayu; Turpie, Bruce; Makarenkova, Helen P.; Masli, Sharmila; Utheim, Tor P.; Dartt, Darlene A.
Abstract: The purpose of this study was to investigate the changes that occur in the lacrimal glands (LGs) in female thrombospondin 1 knockout (TSP1 −/− ) mice, a mouse model of the autoimmune disease Sjogren's syndrome. The LGs of 4, 12, and 24 week-old female TSP1 −/− and C57BL/6J (wild type, WT) mice were used. qPCR was performed to measure cytokine expression. To study the architecture, LG sections were stained with hematoxylin and eosin. Cell proliferation was measured using bromo-deoxyuridine and immunohistochemistry. Amount of CD47 and stem cell markers was analyzed by western blot analysis and location by immunofluorescence microscopy. Expression of stem cell transcription factors was performed using Mouse Stem Cell Transcription Factors RT 2 Profiler PCR Array. Cytokine levels significantly increased in LGs of 24 week-old TSP1 −/− mice while morphological changes were detected at 12 weeks. Proliferation was decreased in 12 week-old TSP1 −/− mice. Three transcription factors were overexpressed and eleven underexpressed in TSP1 −/− compared to WT LGs. The amount of CD47, Musashi1, and Sox2 was decreased while the amount of ABCG2 was increased in 12 week-old TSP1 −/− mice. We conclude that TSP1 is necessary for maintaining normal LG homeostasis. Absence of TSP1 alters cytokine levels and stem cell transcription factors, LG cellular architecture, decreases cell proliferation, and alters amount of stem cell markers. Highlights: Absence of TSP1 alters cytokine levels, morphology, and proliferation in lacrimal glands (LG) of TSP1 −/− mice. Three transcription factors were overexpressed and eleven underexpressed in TSP1 −/− compared to WT LGs. CD47, Musashi1, and Sox2 were decreased TSP1 −/− mice. TSP1 maintains lacrimal gland homeostasis and epithelial/myoepithelial stem/progenitor cell balance necessary for LG regeneration.